Crossroads of faith and creativity in islamic thought, industrial design, and technological art - Awang Besar, Nazirul Mubin; Shariff, Qatrunnisa (Universiti Teknologi MARA, Kedah, 2025)
Islamic thought has significantly influenced various fields, including art, science, and technology, shaping modern industrial design and technological art. At the core of Islamic art and design traditions are values such as balance, harmony, and beauty, which reflect a worldview where creativity is closely linked to spiritual responsibility. This perspective continues to influence contemporary design practices by prioritising ethical considerations, sustainability, and aesthetic values in innovation (Riasat Islam, 2020). During the Golden Age of Islam (8th to 14th centuries), art, design, and science developed in parallel, with scholars like Al- Khwarizmi and Ibn Sina bridging creative expression and technological advancement. Islamic geometric patterns and calligraphy became central to artistic forms, while architectural masterpieces such as the Alhambra and the Suleymaniye Mosque exemplified the convergence of faith and creativity. This period underscores the longstanding relationship between art and science in Islamic thought (Ruggles, 2016).